Zinc oxide nanoparticles in meat packaging: A systematic review of recent literature. (April 2023) - Smaoui, Slim; Chérif, Ichraf; Ben Hlima, Hajer; Khan, Muhammad Usman; Rebezov, Maksim; Thiruvengadam, Muthu; Sarkar, Tanmay; Shariati, Mohammad Ali; Lorenzo, Jose Manuel
Abstract: Questions have been raised apropos food spoilage, which may pose a great hazard to the global environment and human health. Amongst bio-safe material that retains photocatalysis and impacts, photo-oxidizing on biological and species chemical are ZnO nanoparticles (ZnO-NPs). In this respect, this current paper covers a wide range of topics, starting from the ZnO-NPs synthesis and antibacterial potential to their functional application in meat packaging. A deep comparison of the physicochemical properties of ZnO-NPs synthesized through different routers was reported. In addition, a special focus has been given to antibacterial mechanisms that underlie synthesis parameters. This review also examined the ZnO-NPs impact on the chemico–physico–mechanical properties of the functional coatings/films features. Likewise, the employment of ZnO-NPs in meat packaging was also evaluated. As safer nanoparticles, ZnO-NPs enhance stored meat product quality by microflora growth limitation and retards lipid/protein oxidation. Remarkably, active packaging comprising ZnO-NPs, synthesized or not by plants, showed an eco-friendly solution and future alternative in the meat industry. Information about these topics could help students and scientific researchers who are engaged in chemical engineering, chemistry and meat technology communities to approach the complex thematic of ZnO-NPs. Highlights: The employment of ZnO-NPs in meat packaging was also evaluated. ZnO-NPs impact on the mechanical properties of the functional coatings/films features. Active packaging comprising ZnO-NPs showed an eco-friendly solution. ZnO-NPs delays the microflora growth limitation and retards lipid/protein oxidation. ZnO NPs synthesis and antibacterial potential to their functional application in meat packaging.